Characteristics of Falls Among the Elderly During the COVID-19 Pandemic Lockdown: Covid-19 falls among elderly - Isha Tajane; Julia Jossy; Priya Gupta; Prachi Jadhav (ACHSM, 2021)
Background: Every year millions of older people experience a fall. There are many reasons associated as to why a fall occurs in elderly: musculoskeletal weakness, balance issues etc. A fall can lead to a serious injury or mortality depending on the type and impact of the fall. As the environment for the elderly was restricted to their homes during the Covid-19 pandemic, this study aimed at assessing the characteristics of falls during the pandemic. Materials and methods: 60 elderly individuals aging 60 years and above participated in the study. This included 36.7% males and 63.3% females. A pre-validated questionnaire was used to assess the characteristics of falls. Result: Fear of fall was not experienced or was same as before the lockdown however the fall percentage decreased by 7% during the lockdown. Conclusion: Falls among the elderly decreased during the Covid-19 pandemic lockdown.